GIS-based landslide susceptibility mapping in IV Koto, Matur, and Tanjung Raya Subdistricts of Agam Regency, West Sumatra - Maiyudi, Riko; Octova, Adree; Anaperta, Yoszi Mingsi; Gusman, Mulya; Yulhendra, Dedi; Naldo, Exwil; Baron, Adhitya (Journal of Degraded and Mining Lands Management, 2026)
Landslides are a recurrent hazard in West Sumatra, driven by steep slopes, high rainfall, and expanding human activity on unstable terrain. This study assesses landslide susceptibility in IV Koto, Matur, and Tanjung Raya Subdistricts of Agam Regency, West Sumatra using a Geographic Information System (GIS) framework. Slope gradients were derived from DEMNAS (Digital Elevation Model Nasional), land use data were reclassified based on expected stability effects, and rainfall statistics were discretized into intensity classes. These standardized layers were integrated through a weighted overlay to produce a susceptibility surface, subsequently partitioned into two classes: vulnerable and very vulnerable. The results highlight elongated belts of very vulnerable terrain where steep slopes coincide with high rainfall and disturbed land covers such as settlements, open fields, and mining areas. Cross-sectional profiles with gradients of   40.9-56% confirmed the geomorphic plausibility of the mapping. The outputs provide actionable guidance for spatial planning, disaster preparedness, and conservation, while offering a transparent baseline for more advanced susceptibility models as data availability improves.